Immediate Implant Placement in Fresh Extraction Socket - Mohammed Majid Abdulmunem; Jamal Abid Mohammed (College of Dentistry/ University of Baghdad, 2016)
Background: In the traditional protocol, the patient should wait after extraction up to six months to place the dental implant in healed bone, this waiting time accompanied by varying degrees of alveolar bone changes. In order to overcome these problems, immediate implant placement in the fresh extraction socket was introduced. The Aim of this study was to evaluate the outcome of the immediate implant placement utilizing Resonance Frequency Analysis (RFA) to quantify implant stability and osseointegration. Materials and Methods: A total of (23) patients participated in the study, receiving (44) implants placed in the sockets of teeth indicated for extraction. Clinical and radiographic preoperative assessment was accomplished for each patient, β-TCP (combined with collagen membrane) was used to fill gaps ≥ (2 mm) and to repair bone defects. Implant stability quotient (ISQ) values were measured for the implants at baseline and at 16 weeks. Postoperative clinical and radiographic evaluation was applied for each patient. Results: A total of (22) patients received (41) implants completed the follow-up period, all these implants survived (100% survival rate) with no signs and symptoms of failure. The mean of ISQ value at baseline was (65.32±9.50), the mean of ISQ value at 16 weeks was (69.78±7.15), paired samples statistic showed high significant increase in the implant stability (P